HOMO MIGRANS;MODELING MOBILITY AND MIGRATION IN HUMAN HISTORY - MEGAN J. DANIELS (STATE UNIV OF NEW YORK PR, 2022)
Addresses the revolutionary impact of genetics, isotopes, and data science on the study of migration and mobility in past human societies.